СТРУКТУРА УГРУПОВАННЯ ФІТО- ТА ЗООПЛАНКТОНУ ШЕЛЬФОВИХ ВОД ПІВНІЧНО-ЗАХІДНОЇ ЧАСТИНИ ЧОРНОГО МОРЯ ВЛІТКУ 2019 РОКУ - Грандова, М.О.; Набокін, М.В.; Дядичко, В.Г. (Marine Ecological Journal, 2023)
The article presents the results of studies of phyto- and zooplankton of North-Western Black Sea shelf in the summer of 2019. For phytoplankton, 117 taxa from 13 classes were noted, Bacillariophyceae and Dinophyceae dominated. The average abundance was 123 thousand cells*L-1, the average biomass was 713 mg*m-3. Pseudosolenia calcar-avis (Schultze) B.G. Sundström, 1986 and Tripos muelleri Bory de Saint-Vincent, 1826. dominated by biomass. The spatial distribution of chlorophyll-α concentration approximately coincides with the distribution of phytoplankton biomass. For zooplankton, 30 taxa were noted, the basis of diversity belongs to Copepoda and Cladocera. The average abundance was 10816 ind* m-3, the average biomass was 607 mg* m-3. The genera Acartia, Oithona, Centropages, Penilia avirostris and various species of the family Podonidae dominated at all the stations. In transitional waters, the contribution of freshwater phytoplankton species to biomass did not exceed 2%, the basis of biomass was formed by marine species.Despite this, in ShW_UA_1 there was a significant negative correlation between biomass and salinity (r = -0.87). In the shelf waters of the marine zone, the contribution of freshwater species to the total biomass did not exceed 0.1%, the correlation between salinity and biomass was absent (r = 0.26). At most offshore stations, brackish and freshwater zooplankton taxa were absent. There was no significant correlation between salinity and zooplankton biomass. As we approach the estuaries, the biomass of zooplankton decreases with increasing abundance. There is a high negative correlation between the ratio of zooplankton abundance to its biomass and the distance to the nearest estuary (r = - 0.90), for phytoplankton this correlation is r = - 0.534. For most offshore stations and horizons, water quality by phytoplankton indicators can be assessed as GES, by zooplankton indicators, as non-GES.